Research and development of Ce-containing Nd2Fe14B-type alloys and permanent magnetic materials. Issue 10 (October 2017) - Jiang, Qingzheng; Zhong, Zhenchen
Abstract: Much demanded and overused are the critical rare-earth elements such as Pr, Nd, Dy, and Tb with increasing need of NdFeB-type rare-earth permanent magnets in the enlarging application areas, developing new high-tech industries, and emerging cutting-age frontiers. The balance and efficient use of rare-earth resources comes into being the national strategy, national defense, and border safety for many major countries and regions in the world. (Nd, Ce)FeB-based permanent magnetic materials, which can not only reduce cost but also offer a feasible way for integrated and effective utilization of rare earth resources, have received much attention in recent years. The existence of CeFe2 and the mixed valence state of Ce in CeFeB compound, the different metallurgy behavior and the particular processing as well as potential various magnetic-hardening mechanisms, however, make it quite different from Nd-based alloys. For instance, the coercivity of Ce-containing magnets in some certain composition range, is even higher than that of the counterpart pure Nd-based magnets though the Ce-containing magnets possess inferior intrinsic properties. Consequently, it is very important to design proper composition and structure, optimize processing, and analyze the mechanisms in depth for this kind of magnet. High performance and cost-effective magnets can be fabricated if we can make full use of the composition's inhomogeneous and abnormal coercivity variation of the Ce-containing permanent magnets. In this paper, we have summarized the phase structures, magnetic properties and microstructures of (Nd, Ce)FeB-based permanent magnetic materials to shed light on further research and development of this type of so-called "gap magnet".